Imagination Therapy through Art and Technology: A Collaborative Mental Health Intervention - Aditya Wahyu Ramadhan; Eko Supriyanto; Handriyotopo Handriyotopo (SAINTIS Publishing, 2025)
This research explores imagination therapy as a creative method aimed at providing visual therapy for ten schizophrenic clients, referred to as